A Framework for Communities of Practice in Learning Organizations. Issue 1 (January 2015) - Jagasia, Jyoti; Baul, Utpal; Mallik, Debasis
Knowledge Management (KM) helps organizations adapt, survive, and compete in a discontinuous and ever-changing business environment. Essentially, this involves a set of organizational processes which harness the data and information processing capacity of information technologies, and the creative and innovative capacity of human beings. Communities of practice (CoP) are the social tools to connect, engage, and share knowledge in organizations. The research reported here aims to examine the critical factors for successful implementation of CoPs. Based on a survey of 223 respondents who have participated in successful organizational initiatives related to KM and CoPs, this study uses a regression model to analyze the findings. The results identify four essential factors which lead to an effective CoP implementation—providing proper community support, people factors, alignment of the KM initiative with the business strategy, and key KM processes. The results strongly support the appropriateness of the research model in identifying the success factors. Finally, this study discusses the implications of these findings and offers directions for future research.